Chemical constituents of cuscuta campestris yuncker / Leong Sow Tein - Leong, Sow Tein (2012)

(untitled)
Cuscuta campestris Yuncker (Golden Dodder) is commonly known as Rumput Emas in Malaysia. Cuscuta campestris is a weed which has become a serious threat to agriculture. A phytochemical study on the chemical constituents of sample (C. campestris) was performed. The sample was collected along the roadside at Pekan Nanas, Pontian, Johore (N 1° 20’ to N 2° 35’ - E 102° 28’ 59.9” to E 104° 33’ 52.9”). After separation from host plants, the sample was dried and extracted with ethanol. Chromatography method was used in separation and isolation of chemical constituents of sample. Six compounds were isolated viz., sitosterol 99, pinoresinol 18, arbutin 22, kaempferol 30, quercetin 53, and astragalin 50. The structures of these compounds were elucidated through NMR spectra. The allelopathic potential of ethanolic extract of sample was manifested through inhibition of seed germination and seedling growth. The ethanolic extract of Cuscuta campestris inhibited lettuce seed germination when exposed to higher concentration (500 ppm and above). The growth of shoot length and root of all three crops (lettuce, radish and weedy rice) showed significant reduction after treatment with the ethanolic extract. The same bioassay method was used to test the potential of three allelochemicals isolated, viz. kaempferol 30, sitosterol 99 and pinoresinol 18. All the samples showed stimulatory result on plant growth which could be due to hormesis effect. The response of all assayed species was dose-dependent.